2020
DOI: 10.1007/s13304-020-00911-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic rectal resection: oncologic outcomes

Abstract: Robotic surgery has progressively gained popularity in the treatment of rectal cancer. However, only a few studies on its oncologic effectiveness are currently present, with contrasting results. The purpose of this study is to report a single surgeon’s experience on robotic rectal resection (RRR) for cancer, focusing on the analysis of oncologic outcomes, both in terms of pathological features and long-term results. One-hundred and twenty-two consecutive patients who underwent RRR for rectal cancer from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…All surgical procedures were performed by two senior surgeons with an extensive experience in colorectal surgery, according to standardized surgical steps as previously reported [18,19]. A mechanical bowel preparation was prescribed and performed two days before surgery in all cases.…”
Section: Selection For Neoadjuvant Treatment and Surgical Techniquementioning
confidence: 99%
“…All surgical procedures were performed by two senior surgeons with an extensive experience in colorectal surgery, according to standardized surgical steps as previously reported [18,19]. A mechanical bowel preparation was prescribed and performed two days before surgery in all cases.…”
Section: Selection For Neoadjuvant Treatment and Surgical Techniquementioning
confidence: 99%
“…8 Robotic rectal resection has a low rate of positive circumferential resection margins, a high rate of appropriate total mesorectal excision, and good overall and disease-free survival. 9 Even when focusing on abdominoperineal resection, robotic surgery has demonstrated better short-term outcomes than laparoscopic surgery, suggesting that it could be a useful approach. 10 However, one of the disadvantages of robotic surgery is the high cost associated with its implementation and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A large meta‐analysis by Khajeh et al showed that robotic surgery had better outcomes than the laparoscopic approach in terms of bleeding, the need for reoperation, and complete tumor resection 8 . Robotic rectal resection has a low rate of positive circumferential resection margins, a high rate of appropriate total mesorectal excision, and good overall and disease‐free survival 9 . Even when focusing on abdominoperineal resection, robotic surgery has demonstrated better short‐term outcomes than laparoscopic surgery, suggesting that it could be a useful approach 10 …”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies investigated the association between postoperative hyperglycemia and long-term outcomes. In a retrospective study, 173 patients without diabetes underwent curative gastric cancer surgery and 104 patients were included in the final analysis after propensity score matching; postoperative hyperglycemia (defined as at least one blood glucose ≥ 7.8 mmol/L within 72 h) was associated with worse 5-year overall survival and worse 5-year disease-free survival (21). In the present study, the sample size and the number of end-point events were far larger than in the above one.…”
Section: P-valuementioning
confidence: 99%
“…In a retrospective study of 505 patients following peripheral arterial bypass surgery, immediate postoperative hyperglycemia (≥7.8 mmol/L) was associated with an increased risk of long-term amputations (13). In another retrospective study, 104 patients were included in the analysis after propensity score matching; those with postoperative hyperglycemia (≥ 7.8 mmol/L) had worse long-term survival after gastric cancer surgery (21). Whereas a 44-month follow-up of 189 patients enrolled in a randomized trial showed that strict (5-6.7 mmol/L) compared with liberal (6.7-10 mmol/L) glucose management did not change long-term survival and quality of life after coronary bypass surgery (22), but the trial was seriously underpowered.…”
Section: Introductionmentioning
confidence: 99%